Analysis of Regional Financial Report Disclosure Factors: A Literature Review - Ferryansah; Evana, Einde; Dharma, Fitra (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research looks at various factors influencing regional government financial report disclosure in Indonesia. The method used is a literature review using the SINTA database with a publication period of ten years. The results show that good audit opinions, a high level of independence, and effective regional revenue management positively impact the disclosure of regional government financial reports. Other factors, such as political pressure, population size, and regional wealth, also play an important role in shaping transparency. Increasing openness of financial information at the regional level strengthens accountability and builds public trust in local government. Based on these findings, it is known that it is important for local governments to pay attention to factors such as audit opinion, level of independence, and revenue management to increase financial report disclosure. In addition, understanding political pressures, population size, and regional wealth is also needed to form effective transparency policies. Increasing the transparency of financial information at the regional level is expected to strengthen government accountability and build public trust, support good governance, and increase the efficiency of regional financial management